THEATRE AND SOCIAL INTEGRATION: A STUDY OF RADICAL ALTERNATIVES IN TWO SELECT PLAYS - Nwani, Treasure Okoronkwor (EBSU Journal of Social Sciences and Humanities, 2025)
High-profile corruption, injustice, moral decadence, insurgency among the numerous challenges facing the country present themes for the theatre. Over the years, theatre has served as an instrument of socio-political revolution around the world. Though critical works abound on the ideology as well as the approaches for social integration in play texts, studies have not sufficiently examined the collectivism in the role of characters as revolutionary alternatives to the socio-political and economic maladies. It is on this note that this paper critically focuses on the use of collective heroism in achieving radical change in the plays under study. In doing this, this paper engages the social criticism theory and the Marxist theory predicated on content analysis of texts to explore the use of revolutionary characters as social vilification of the Nigerian polity. Nwokedi and Hangmen also Die are reviewed as plays that have been proactively employed to unearth the social dislocations and decadence of the society with the vision to bring about social conscientisation, edification and mass action for social change. The findings reveal that a radical play fully identify with human right activism to release the masses from the clutches of bad governance. Also, findings show that the mass of the economically deprived people need to rise up collectively as heroes to save themselves instead of waiting for an individual to do it for them. The paper concludes that the select plays led a new tradition in the reformation of the body polity of the nation.